Current Trends Influencing the Competitiveness of International Tourism - VERETEKHINA, Svetlana V.; MEDVEDEVA, Alla V.; VINICHENKO, Mikhail V.; DEMCHENKO, Tatiana S.; KARYAGINA, Tatyana V.; MAKUSHKIN, Sergey A. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
Relevance of the research topic is conditioned by the need for scientific and methodological support of the competitiveness of international tourism. The article analyzes modern trends in international tourism. The preferences of the international tourist are determined. Favorable factors that determine the superiority of international tourism are determined. During the research, a systematic analysis was carried out, which makes it possible to comprehensively consider the problems of international tourism, analyze the advantages and disadvantages, and draw up reasoned conclusions. The article analyzes the state of competition in the market using the following indicators. The first indicator is the market concentration ratio (CR – Market Share Concentration Ratio). The second indicator is the index of the market concentration of Herfindahl-Hirschman (HHI – Herfindahl-Hirschman Index). Franchising and reengineering of processes are considered as tools for increasing the competitiveness of international tourism. Scientific novelty is the definition of new trends affecting the competitiveness of international tourism, based on calculated indicators. The materials of the article are of practical importance for increasing the competitiveness of enterprises and organizations of international tourism of various countries.